Development of a Water Detection System - Schack, Christoffer (2012)
Every year, more than 100.000 water damages occur in buildings all over Sweden and about three per cent of the households are being affected. The cost of the damages reaches up to as high as five billion SEK (Säker Vatten)By applying the theory and methods learned during the Master’s programme in Industrial Design Engineering at Luleå University of Technology together with the Product Science Department at Securitas Direct AB in Malmö a water detection system customized for the Verisure platform has been developed.The result is a passive water detection system with both internal and external water sensors and it wirelessly communicates with the central unit in Securitas Direct’s Verisure platform and uses the platform’s alarming system. It is rather small compared to its competitors and the installation and handling of the device requires no specific skills or prior experience of water detectors. The small size and optional external sensors allows for monitoring in narrow areas where other systems will not fit. Validerat; 20120614 (anonymous)